Chemical imprinting meets nanotechnology: Ultra-sensitive monitoring of beta-endorphin - Ankita Ghosh; Ramesh Chandra; Nidhi Chauhan (Talanta Open)
Beta-endorphin (BE) is an endogenous opioid peptide (EOP) produced in the anterior pituitary gland and hypothalamus. Beta-endorphin is a vital neurotransmitter involved in physiological processes including relief the pain, boosting memory, and regulating mood. BE is a happy hormone that reduces the chance of depression and anxiety. BE analysed by traditional laboratory techniques like LC-MS, ELISA and radioimmunoassay is reliable; however, there are certain limitations including time consumption, device complexity, cost and availability. This study aims to develop a self-monitoring molecularly imprinted polymer-based (MIP) biosensor for sensitive, selective and rapid detection of BE. The nanocomposite TiO2/MoS2 was electrochemically deposited on the screen-printed electrode using cyclic voltammetry (CV) to enhance the conductivity and surface area to immobilize MIP. The MIP was electrochemically deposited at voltage range 0.2 to -0.6 V using CV for 20 cycles at scan rate 50 mV/s on the modified TiO2/MoS2/SPE. MIP is a synthetic bio-recognizing element that provides high selectivity for BE over other structurally similar molecules. The developed sensor MIP@TiO2/MoS2/SPE exhibits sensitivity of 0.475 µA/pM, the limit of detection (LOD) of 0.1pM and a detection range of 0.1pM and 200pM. This is novel, innovative and cost-effective point of care device developed for the rapid and real time detection of BE.